ECG characteristics according to the presence of late gadolinium enhancement on cardiac MRI in hypertrophic cardiomyopathy. Issue 1 (5th August 2014) - Grall, Sylvain; Biere, Loïc; Clerfond, Guillaume; Mateus, Victor; Prunier, Fabrice; Furber, Alain
Abstract : Background: Late gadolinium enhancement (LGE) on cardiac MRI (CMR) has been described as an independent predictive factor of cardiovascular events among patients with hypertrophic cardiomyopathy (HCM). LGE and Q waves are considered as myocardial scar markers but their relation in the context of HCM is poorly established and has to be more supported. The objective of the study was to compare ECG findings in the presence or absence of LGE. Methods: 42 patients with HCM confirmed by CMR were included in the study. ECG abnormalities including abnormal Q waves and five ECG scores of left ventricular hypertrophy were assessed and compared according to LGE presence and its extension. Some CMR features, such as septal to posterior wall thickness ratio, were also studied according to the presence of LGE and the presence of abnormal Q waves. Results: Abnormal Q waves were more prevalent in the LGE (+) group (60% vs 12%; p=0.002), but there was no correlation between location of Q waves on ECG and territory of LGE on CMR. Among patients with LGE, quantitative analysis of LGE was not different in the presence or absence of Q waves. In contrast to the LGE mass, septal to posterior wall thickness was higher in patients with abnormal Q waves (2.3±0.7 vs 1.6±0.5; p=0.012). Conclusions: Although abnormal Q waves were more prevalent in the presence of LGE, no correlation was found with the LGE location and extent. These data suggest that abnormal electrical activation of the hypertrophied ventricular septum represented by a high septal to posterior wall thickness ratio seems to be an important mechanism of abnormal Q waves in HCM.